2011
DOI: 10.1080/08927014.2011.553717
|View full text |Cite
|
Sign up to set email alerts
|

Larval metamorphosis of the mussel Mytilus galloprovincialis Lamarck, 1819 in response to neurotransmitter blockers and tetraethylammonium

Abstract: The metamorphic response of pediveliger larvae of Mytilus galloprovincialis to the neurotransmitter blockers chlorpromazine, amitriptyline, rauwolscine, idazoxan, atenolol and butoxamine, and to tetraethylammonium chloride (TEA) was investigated through a series of bioassays. Chlorpromazine, amitriptyline and idazoxin inhibited larval metamorphosis induced by 10⁻⁴ M epinephrine. The concentration that inhibited metamorphosis by 50% (IC₅₀) for chlorpromazine and amitriptyline was 1.6 x 10⁻⁶ M and 6.6 x 10⁻⁵ M, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Following the primary settlement, these plantigrades can detach from their byssal threads and resettle to a new location (Bayne, 1964;Kavouras and Maki, 2003;Petrone, 2013). A number of researchers have focused on larval settlement of many species of mussels, such as Mytilus edulis (Dobretsov and Qian, 2003), Mytilus galloprovincialis (Satuito et al, 1995;Bao et al, 2007;Yang et al, 2007Yang et al, , 2011, Mytilus coruscus (Wang et al, 2012;Yang et al, 2013a,b), Perna canaliculus (Ganesan et al, 2010;Young et al, 2011), Aulacomya maoriana . However, the interaction between environmental factors and mussel plantigrade settlement has been little investigated.…”
Section: Introductionmentioning
confidence: 97%
“…Following the primary settlement, these plantigrades can detach from their byssal threads and resettle to a new location (Bayne, 1964;Kavouras and Maki, 2003;Petrone, 2013). A number of researchers have focused on larval settlement of many species of mussels, such as Mytilus edulis (Dobretsov and Qian, 2003), Mytilus galloprovincialis (Satuito et al, 1995;Bao et al, 2007;Yang et al, 2007Yang et al, , 2011, Mytilus coruscus (Wang et al, 2012;Yang et al, 2013a,b), Perna canaliculus (Ganesan et al, 2010;Young et al, 2011), Aulacomya maoriana . However, the interaction between environmental factors and mussel plantigrade settlement has been little investigated.…”
Section: Introductionmentioning
confidence: 97%
“…The results of the present study indicate greater sensitivity in freshwater mussels (LC50 values of 0.3-0.8 mg/L) than in daphnids. Acting as a neurotransmitter blocker, amitriptyline has been shown to inhibit larval metamorphosis in the marine mussel Mytilus galloprovincialis with a 50% inhibitory concentration of 2.6 Â 10 À5 M ($7 mg/L) [56]. Similarly, Di Poi et al [57] reported adverse effects of amitriptyline on the embryo-larval development of the Pacific oyster Crassostrea gigas, with an EC50 value of 0.19 mg/L.…”
Section: Toxicitymentioning
confidence: 99%
“…The settlement and metamorphosis of marine invertebrates are induced by K + (Yool et al, 1986). It is generally believed that K + can depolarize the cell membrane, resulting in the induction of larval settlement and metamorphosis (Baloun and Morse, 1984), and that tetraethyl-ammonium (TEA) can control this induction by K + (Yang et al, 2011). However, previous research on oyster settlement and metamorphosis has mainly focused on the roles of adrenaline and dopamine (Steven and Dale, 1986), while the effects of K + on settlement and metamorphosis of Pacific oyster larvae remain unclear.…”
Section: Introductionmentioning
confidence: 99%